Bridging the Age-based Digital Divide: An Intergenerational Exchange during the First COVID-19 Pandemic Lockdown Period in Ireland. Issue 2 (3rd April 2022) - Flynn, Sandra
ABSTRACT: This qualitative study explored the digital communication skills assistance provided by young adults in the age range 18 to 25 years to older family members during the period of the first COVID-19 pandemic lockdown in Ireland in 2020. Data were collected from a sample of young adults (n = 248) using an online survey instrument to explore their learnings from the intergenerational exchange. The study found that young adults who assisted their older family members considered the learning experience to be successful and were rewarded with reciprocal benefits. This study contributes to the field of intergenerational research by exploring the perspectives of young adults involved in an intergenerational exchange to support the digital skills of their older adult family members in Ireland.